Examination Of Online Submission And Peer Review Systems In Terms Of Author Role Capability In Iranian Medical Journals - Fereydoon Azadeh; Alireza Hemmati; Seyed Javad Ghazi Mirsaeid; Tania Azadi (Tehran University of Medical Sciences, 2015)
Background and Aim: Online submission and peer review systems are formal channels of communication among authors, journal editorial boards, and reviewers. The review process starts after authors submit their manuscripts. The aim of this study is to examine the online article submission and peer review systems in terms of the capability in medical journals of Iranian Ministry of Health, and Medical Education. Materials and Methods: In this descriptive survey study, 199 approved Iranian medical journals were examined so that the characteristics of online submission and peer review systems could be investigated. To study author role features, a checklist was developed by the researcher. The data were analyzed by SPSS 18 and Microsoft Excel 2007. Results: The online submission and peer review systems considered in this study had most (84%) of the features of the author role. Among the systems reviewed, Kowsar system had the highest number of features. Conclusion: The results show that the studied systems consider some, but not all, of the required features. To meet the maximum required features of the author role, it seems necessary to take all standard research criteria into account